Alternatives to Deconchy's 'Constraints' - Tilander, Ake (The international journal for the psychology of religion, 1991)
Deconchy (this issue) suggests a research paradigm for the psychology of religion that is based on a set of constants. It is a deterministic, natural-science model that has definite limitations due to the nature of the human being, and it has not always been fruitful for the study of religion. The nondeterministic, creative nature of human beings makes it difficult to force them into cause-and-effect laws that are invariant. Deconchy ignores other under- standings of causality that should be considered. These include finality, home stasis, and archetypes. Considering these is offered as a complement to Deconchy's perspective.